Training adaptation and biological changes among well-trained male triathletes - Rowbottom, D. G.; Keast, D.; Garcia-Webb, P.; Morton, A. R. (Medicine & Science in Sports & Exercise, 1997)
The distinction between training and overtraining responses is an important prerequisite for any potential marker for monitoring overtraining in athletes. In this study, eight well-trained male triathletes undertook physical performance assessments, at 6 weekly intervals, throughout a 9-month intensive training season. At each assessment, a resting blood sample was obtained for determination of a number of biological parameters previously associated with overtraining. All athletes produced significant (P < 0.05) improvements in running speed at anaerobic threshold (ATRS) from 15.6 +/- 0.2 k.h-1 at the start of the season to 16.6 +/- 0.6 k.h-1 at the time of major competitions. This improvement in performance was taken as evidence of well balanced training programs. Significant changes (P < 0.05) in plasma glutamine and plasma uric acid concentrations were observed during the training season, and both correlated moderately with ATRS (r = 0.365 and r = -0.328, respectively). None of the other parameters measured showed any significant changes during the training season. The elevations in plasma glutamine concentration observed in response to long-term balanced training may be distinguishable from previous reports of decreased glutamine concentrations in overtrained athletes, making it a potentially valuable tool in the monitoring of overtraining in athletes.